2000
DOI: 10.1523/jneurosci.20-14-05367.2000
|View full text |Cite
|
Sign up to set email alerts
|

TrkB Receptor Ligands Promote Activity-Dependent Inhibitory Synaptogenesis

Abstract: Organotypic cerebellar cultures derived from newborn mice were simultaneously exposed to activity-blocking agents and neurotrophins for 2 weeks. Activity-blocked explants treated with the TrkB receptor ligands BDNF and neurotrophin-4 (NT-4) developed a full complement of Purkinje cell inhibitory axosomatic synapses, as defined ultrastructurally, and displayed control spontaneous cortical discharge rates after recovery from activity blockade. Otherwise untreated activity-blocked cultures and activity-blocked cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 51 publications
6
95
2
Order By: Relevance
“…BDNF promotion of inhibitory axon outgrowth and synapse formation is well characterized in hippocampus, cortex and, in particular, cerebellum in vitro and in vivo (Huang et al, 1999;Marty et al, 2000;Seil and Drake-Baumann, 2000;Yamada et al, 2002). Accordingly, fewer GABAergic synapses are observed in cerebellar slices following scavenging of endogenous BDNF (Seil and DrakeBaumann, 2000) and in conditional TrkB deletion mutants (Rico et al, 2002).…”
Section: Neurotrophins As Synaptic Modulators: Presynaptic Terminal Fmentioning
confidence: 99%
“…BDNF promotion of inhibitory axon outgrowth and synapse formation is well characterized in hippocampus, cortex and, in particular, cerebellum in vitro and in vivo (Huang et al, 1999;Marty et al, 2000;Seil and Drake-Baumann, 2000;Yamada et al, 2002). Accordingly, fewer GABAergic synapses are observed in cerebellar slices following scavenging of endogenous BDNF (Seil and DrakeBaumann, 2000) and in conditional TrkB deletion mutants (Rico et al, 2002).…”
Section: Neurotrophins As Synaptic Modulators: Presynaptic Terminal Fmentioning
confidence: 99%
“…Recent studies have suggested a role for neurotrophins in the growth and refinement of neural connections, 43 dendritic arborization, 17 programmed cell death, 44 cortical lamination, 18,45 synaptogenesis, 46 and in activity-dependent synaptic plasticity. 47,48 Altered expression of NT3, NT4, trkB, and trkC as well as netrin 1 may have numerous potentially deleterious effects on cortical lamination during development. For example, an intriguing study demonstrated that administration of exogenous NT4 to organotypic cortical slice cultures results in dyslamination and neuronal heterotopia within cortical layers I to II.…”
Section: Altered Neurotrophin Expression and Aberrant Cytoarchitecturmentioning
confidence: 99%
“…50 Cell culture experiments revealed reduced survival by trkBϪ/Ϫ cortical neurons, a quantitatively significant defect in the formation of dendrites, and a significant reduction in neurite outgrowth by surviving trkBϪ/Ϫ neurons. 48 Reduced levels of netrin1 are associated with impaired axon pathfinding and aberrant neuronal migration. 51 …”
Section: Altered Neurotrophin Expression and Aberrant Cytoarchitecturmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evidence has shown that BDNF modulates the level of functional inhibition in an activity-dependent manner by regulating the number of GABAergic interneurons (Rutherford et al, 1997). Neuronal activity also modulates inhibitory synaptogenesis (Seil and Drake-Baumann, 1994;Marty et al, 2000), and this synapse formation is regulated by BDNF (Seil and Drake-Baumann, 2000). However, the long-term effects of BDNF on the strength of inhibitory synapses are unclear.…”
Section: Introductionmentioning
confidence: 99%